Juvenile amyotrophic lateral sclerosis associated with biallelic c.757delG mutation of sorbitol dehydrogenase gene. Issue 5 (3rd July 2022) - Bernard, Emilien; Pegat, Antoine; Vallet, Anne-Evelyne; Leblanc, Pascal; Lumbroso, Serge; Mouzat, Kevin; Latour, Philippe
Abstract: Mutation in the sorbitol dehydrogenase gene ( SORD ) has been recently described to cause axonal Charcot-Marie-Tooth disease (CMT), intermediate CMT, and distal hereditary motor neuropathy (dHMN). We herein report the case of a 24-year-old patient diagnosed with juvenile amyotrophic lateral sclerosis (JALS) who carried the homozygous c.757delG mutation in SORD . No other pathogenic variant in frequent JALS-causative genes was found. Our findings expand the phenotype related to SORD mutation, a new and potentially treatable genetic disease.